Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393l